Sexisms on Facebook Page Threads of Xyriel Manabat: A Linguistic Analysis - Kathleen Joy Asarcon; Kaye Buhia; Marites An Quimbo; Jelyn Pepito; Joemar Minoza (Randwick International of Education and Linguistics Science Journal, 2024)
Linguistic sensitivity is crucial in shaping individuals' thoughts, perceptions, and attitudes. The impact of language influences the creation of opportunities or the imposition of boundaries. This study delves into the realm of sexist language on the Facebook Page threads of the Filipina Child Star Xyriel Manabat, exploring both linguistic and non-linguistic aspects. Drawing on Mill's sexist language typology and Herring et al.'s framework for non-linguistic features, five posts from 2021-2022, gathering the 50 most engaging comments were analyzed. Of these, 36 comments exhibited sexist language. The findings identified five overt forms of sexism, including Naming, Insult terms, Semantic Derogation, and generic Pronouns, while indirect sexism manifested in Humor and Presupposition. Non-linguistic features, such as Emoji and Emoticons, Stickers and GIFs, Images, and Videos, were also noted in sexist comments. The conclusion drawn is that Xyriel Manabat's Facebook page comment sections contain sexist languages, characterized by specific linguistic and non-linguistic features. The study advocates for the use of gender-fair language in social media and educational settings, emphasizing the need for linguistic sexism awareness. Additionally, it encourages future research to explore other platforms and materials for comparative analysis, aiming to contribute to a broader understanding of linguistic dynamics in contemporary communication.